Prevalence and distribution of antibiotic resistance in the water environment of sea bass (Lateolabrax maculatus) breeding area in spring in South China - Lin, Ziyang; Deng, Yiqin; Su, Wenxiao; Wang, Qian; Chen, Haoxiang; Sun, Yun; Feng, Juan (Frontiers in Marine Science, 2023)
Antibiotic resistance represents a global health crisis for humans, animals, and the environment. However, few studies address the abundance and distribution of the environmental bacterial antibiotic resistance associated with farmed fish during the early breeding stages and their relationship with aquaculture environment. In this study, culture-dependent methods and gene chip technology were respectively used to identify and detect cultivable heterotrophic antibiotic resistant bacteria (ARB) and antibiotic resistance genes (ARGs) of water samples from 20 sea bass-rearing ponds in spring in Zhuhai, China. Meanwhile, the relationships among ARGs, ARB, and water nutrients were elucidated. The results showed that bacterial resistance to erythromycin and sulfamethoxazole with trimethoprim was generally high (mean 48.15% and 18.07%, respectively), whereas resistance to rifampicin, florfenicol, ciprofloxacin, and enrofloxacin was generally low (mean 5.46%, 2.16%, 1.43%, and 0.16%, respectively). Acinetobacter sp. (42.31%) and Pseudomonas sp. (25.74%) were the dominant ARB, and most cultivable ARB were opportunistic pathogens. The abundance of sul family genes was higher than that of other tested ARGs. ARGs and ARB were mainly affected by NO3– and PO43–, with PO43– generally positively correlated, whereas NO3– was negatively correlated, with ARGs and ARB. Thus, recommendations for the control of antibiotic resistance risk can be made by understanding the resistance profile of the aquaculture environment.